PENGARUH FINANCIAL LEVERAGE, INVESTASI, LIKUIDITAS, DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI) - Meithasari, Dian; Djazuli, Atim (Jurnal Ilmiah Mahasiswa FEB, 2014)
A company sets earning policy to manage its earning which allocated to two components  namely  dividend  and  retained  earning.  Dividend  is  a  part of earning available for stockholders. Retained earning is a part of earning retained to  be  reinvested  for  growing  the  company.  The  purpose  of  this  research  is  to understand  the  way  financial  leverage,  investment,  liquidity,  and  profitability influence the company’s dividend policy. This  is an explanatory  research, using 19 manufacturing  companies  listed  in  Indonesian Stock Exchange  from 2008 up to 2010 as samples. Type of data  that  is used  in  this research  is panel data and quantitative  data  from  secondary  source.  This  research  uses  double  linear regression analysis by SPSS  test considering  the classic assumption  test, namely normality, multicollinearity,  heterocedastity,  and  autocorelation,  continued with hypothesis  test,  namely  F  test  and  t  test.  Result  shows  that  financial  leverage, investment,  liquidity,  and  profitability  don’t  give  significant  impact  on  dividend policy simultaneously and partially.